Offspring epigenetic markers at birth related to gestational BMI predict offspring BMI‐trajectories from infancy to 26 years - Vimala Devi Janjanam; Susan Ewart; Hongmei Zhang; Yu Jiang; Hasan Arshad; Ali H. Ziyab; Wilfried Karmaus (Wiley, 2023)
Abstract Objective To date, epigenetic studies identified differential DNA methylation (DNAm) related to gestational‐body mass index (BMI) in offspring at birth. This study investigated whether the identified DNAm in offspring were also associated with BMI trajectories from infancy to age 26 years. Methods Data of 794 participants from Isle of Wight birth cohort in UK were investigated to study association between BMI trajectories and DNAm related to gestational‐BMI at birth. Multinominal logistic regression models were applied to test the association between 1090 DNAm sites reported in three prior epigenome‐wide association studies and BMI trajectories. Results DNAm site cg23089913 (NANOS1) and cg13217064 (SOX14) were associated with early persistent obesity (EPO) and delayed overweight (DOW) trajectories respectively. A higher methylation of cg23089913 showed low odds of being in EPO trajectory (OR: 0.84; 95% CI: 0.76-0.93) while higher methylation of cg13217064 resulted in 1.4‐times the odds of being in DOW trajectory when compared to the normal trajectory [Correction added on 22 February 2023, after first online publication: Range of the DNAm site cg23089913 has been changed from 'lower' to 'higher' in the preceding sentence.]. In a gender‐stratified analysis, the odds of developing into DOW was 1.8 times in female participants for cg13217064 while not such association was observed in males. Conclusions Deviations in methylation of cg23089913 (NANOS1) and cg13217064 (SOX14) in newborns may change the risk of having excess body weight.